Analysis of the Risk Factors in Prognosis of Kawasaki Disease With Coronary Artery Lesions - Hu, Jinling; Ren, Weidong (Frontiers in Pediatrics, 2021)
Kawasaki disease (KD) is one of the most common forms of systemic vasculitis in children. Pathological features include extensive inflammation of small and medium blood vessels throughout the body. The primary complication of KD is coronary artery lesions (CALs). A total of 640 children with KD were admitted to the Department of Pediatric Cardiology at Shengjing Hospital of China Medical University from January 2017 to December 2019. These patients comprised 52 coronary artery aneurysm (CAA) cases and 47 coronary artery dilation (CAD) cases. Echocardiography was performed during the acute KD phase and then at 1 month, 3 months, 6 months, 12 months and 24 months after KD onset. Patients were divided into a poor prognosis group (n = 30) and a normal group (n = 69) based on CALs prognosis. Differences in laboratory data, clinical manifestations and coronary artery damage rates were compared between the two groups. Univariate analysis was performed on these data, and an ROC curve was used to analyze the efficacy of each risk factor. Univariate analysis revealed that age (months), number of coronary arteries involved (NACI), IgM, IgA and brain natriuretic peptide (ProBNP) levels were higher in the poor prognosis group compared with the normal group, procalcitonin (PCT) levels in the poor prognosis group were lower than in the normal group (P ＜ 0.05). Conclusion:Age ≥ 18 months, immune disorders and NCAI ≥ 3 were poor prognostic factors of KD children with CALs. These parameters can be used as a reference indicator of early prediction where combined detection might improve the accuracy and sensitivity of prediction. Follow-up should be maintained to monitor changes in the coronary artery by echocardiography.